CONCEPT OF INFORMATION SYSTEM FOR CULTURAL HERITAGE SITES RENOVATION USING AUGMENTED REALITY (Computer systems and information technologies, 2023)
Cultural heritage is key to identity and development. Many valuable objects are affected by time, natural elements and financial lack. Innovative technologies are crucial for their preservation. The paper develops an information system based on augmented reality (AR) for the restoration of cultural heritage. This extends AURA's approach to preserving musical spaces by applying AR to cultural objects. New techniques improve AURA, allowing accurate restoration of objects affected by time. 3D modeling and machine learning allow to create virtual replicas with precision down to the smallest detail. Augmented reality and machine learning open new perspectives for the preservation of cultural values. The paper proposes an innovative approach of using AR for cultural heritage restoration. The authors offer unique solutions for accurate modeling of 3D models of objects. The purpose of the paper is to develop an information system for the restoration of cultural heritage through AR. This will increase the possibilities of preservation and research of values. Using AR and 3D modeling can improve the restoration of objects and provide access for researchers and the public. In future research, the proposed approaches and methods will be implemented to expand the functionality of the information system. This will include developing interactive interfaces for interacting with virtual models of cultural heritage, analyzing data for a deeper understanding of restoration processes and trend detection, as well as integrating cutting-edge information technologies, such as virtual reality and natural language recognition systems, using artificial intelligence. The primary goal is to improve the processes of preserving and studying cultural heritage through the use of modern information technologies.
Keywords: cultural heritage; restoration; innovative technologies; augmented reality (AR); machine learning; 3D modeling; information technologies